Implementasi Kebijakan Percepatan Penurunan Stunting Terintegrasi di Kabupaten Jombang - Firmansyah Aji, Robby; Novaria, Rachmawati (Jurnal Pendidikan Indonesia, 2025)
Stunting is a condition of failure to grow and develop that results in children being shorter than their age due to improper nutritional fulfillment in the first 1000 days of life which affects the physical and functional of the child’s body. Stunting affects Indonesia’s future generations, especially in the golden age of independence in 2045. The Regional Government of Jombang Regency issued Jombang Regent Regulation number 4 of 2022 concerning the Acceleration of Integrated Stunting Reduction in Jombang Regency. Stunted toddlers in early 2024 in Jombang Regency totaled 3639 children under five with a stunting prevalence of 5.85%, which has reached the national target of not exceeding 14%. The purpose of this study is to identify and analyze the implementation of integrated stunting reduction acceleration policies in Jombang Regency and the factors that are inhibiting it. The research uses a qualitative method with data collection carried out by observation, interview, and document study techniques. Using analysis based on the theory of Soren C. Winter (2004) where the success of implementation is influenced by the behavior of relationships between organizations, the behavior of lower-level bureaucrats, and the behavior of target groups. The results of the study show that the Jombang district government has implemented policies quite well, marked by a decrease in stunting cases from 5,509 cases in 2022 to 3,428 as of September 2024. However, there are still indicators of acceleration in stunting reduction that have not met the target, especially related to the behavior of lower-level bureaucrats that need to be improved and improved. Obstacles in the implementation of stunting reduction policies that arise can be used as material for improvement in the future. In line with the conclusion, it is recommended; to optimize the performance of policy actors and improve human resources of lower-level implementers. Collaborate with the public and private sectors so that they can optimize preventive measures to prevent stunting.